Analysis of the Effect of Bridge Height on the Structural Performance of Steel Network-Bound Arch Bridges with Inclination - Daffa Syarif Abdullah; Mohammad Salman Alfarisi; Fajar Tamami; Puput Risdanareni (Universitas Islam Raden Rahmat, Malang, 2026)
Indonesia, with its vast geographical characteristics, requires efficient and sustainable long-span bridges to improve regional connectivity. This study aims to determine the optimal arch height for steel-bound arch bridges with cable network configurations and inward slopes based on structural performance. The analysis was conducted using the finite element method through SAP2000 v.25 on a 150 m span bridge with a cable angle of 74° and variations in arch height of 23 m, 24 m, and 25 m. Structural performance was evaluated based on maximum deflection and normalized structural weight on a scale of 0–1. The results show that increasing the arch height reduces the deflection from 148.55 mm to 131.41 mm with a relatively small increase in weight, which is around 0.5%. The 25 m arch height produces the best performance and is recommended as the optimal configuration for an efficient and sustainable tied arch bridge design.